Penerapan Model Pembelajaran Problem Solving Sebagai Upaya Meningkatkan Prestasi Belajar IPA - Murniati, Made (Universitas Pendidikan Ganesha, 2018)
The learning process in the classroom that makes low student achievement is the basis for making this classroom action research. This research was conducted in class VIII A1 at SMP Negeri 3 Sawan in even semester of 2017/2018 school year. Research data were collected using tests and analyzed using descriptive analysis. After all the processes were carried out which began with planning, continued with the implementation continued with observation / data collection and ended with a reflection that was doing an analysis, it turned out that the data obtained was quite encouraging. Initial values that were initially low were 70.88 with learning completeness only reaching 36.00% and in cycle I it had increased to 75.84 with mastery learning 64.00% and significantly increased in Cycle II to 80.64 100% learning completeness. The data shows the success of this class action research so that the researcher concludes that the Problem Solving learning model is able to improve the science learning achievement of class VIIIA1 students at SMP Negeri 3 Sawan.